Normative Influences on Impulsive Buying Behavior - Rook, Dennis W.; Fisher, Robert J. (Journal of Consumer Research, 1995)
Although consumer researchers have investigated impulse buying for nearly 50 years, almost no research has empirically examined its normative aspects. This article presents conceptual and empirical evidence that consumers' normative evaluations (i.e., judgments about the appropriateness of engaging in impulse buying behavior) moderate the relationship between the impulse buying trait and consumers' buying behaviors. Specifically, the relationship between the buying impulsiveness trait and related buying behaviors is significant only when consumers believe that acting on impulse is appropriate. The findings from two studies across student and retail customer samples converge and support the hypothesized moderating role of consumers' normative evaluations.